(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2019)
Taking all these into account, it is important to increase the fertility of the soil from the erosion process in Ismayilli and to prevent the washing of fodder crops from perennial herbs. The cultivation of these plants in the mountainous regions protects the slopes from the terrible erosion process and provides the animals with a strong fodder. It is proved by the results of the research that restoration of fertility and ecological balance of erosion lands and the implementation of soil-agro-technical measures to increase productivity are of great importance. Due to the application of these measures, I, as a result of improving the water and physical properties of the affected land, prevent surface water flows. In addition, the results of the study have been proven by the fact that, for certain reason, erosion and erosion hazards are most likely to be taken over by the sowing of perennial herbs. Thus, perennial herbs, in particular, accumulate the nitrogen atmosphere of the legumes, enriches the soil with organic matter, accelerates the formation of water-resistant granular - topical structure and improves its water-physical properties, which in turn facilitates the rapid digestion of foodstuffs